ĐẶC ĐIỂM THỊ GIÁC VÀ THÍNH GIÁC CỦA CHÓ BẢN ĐỊA SÔNG MÃ - Ngô, Quang Đức; Bùi, Xuân Phương; Trần, Hữu Côi; Đinh, Thế Dũng; Phùng, Thanh Tùng; Phạm, Thanh Hải; Đàm, Quang Toàn; A. N., Vlaxenko (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
VISUAL AND AUDITORY CHARACTERISTICS OF THE SONG MA NATIVE DOG BREEDEvaluation of the visual and auditory abilities of the Song Ma native dog breed. 30 individuals were monitored from 3 to 12 months of age with a total of 600 tests performed, in which 300 tests determined the distance of sight and 300 tests determined the hearing distance of Song Ma dogs. The tests were carried out at the kennel of the Joint Vietnam-Russia Tropical Science and Technology Research Centre, Yen Binh Commune, Thach That District, Hanoi City, in daytime conditions: not too sunny, no rain, light wind. At different ages, the visual and auditory abilities of Song Ma native dogs are also different and increase with age (p ≤ 0,05). These abilities become stable at 11, 12 months of age. For the Song Ma breed, the average farthest seeing distance is 245.60 m, the average farthest hearing distance is 702.57 m. There was no statistically significant difference between male and female individuals of this breed (p > 0,05).